Purification of ribonucleotide reductase subunits Y1, Y2, Y3, and Y4 from yeast: Y4 plays a key role in diiron cluster assembly - Nguyen, Hiep-Hoa T. (The National Academy of Sciences, 1999)
Ribonucleotide reductases (RNRs) catalyze the conversion of nucleotides to deoxynucleotides. Class I RNRs are composed of two types of subunits: RNR1 contains the active site for reduction and the binding sites for the nucleotide allosteric effectors. RNR2 contains the diiron-tyrosyl radical (Y⋅) cofactor essential for the reduction process. Studies in yeast have recently identified four RNR subunits: Y1 and Y3, Y2 and Y4. These proteins have been expressed in Saccharomyces cerevisiae and in Escherichia coli and purified to ≈90% homogeneity. The specific activity of Y1 isolated from yeast and E. coli is 0.03 μmol⋅min(−1)⋅mg(−1) and of (His)(6)-Y2 [(His)(6)-Y2-K387N] from yeast is 0.037 μmol⋅min(−1)⋅mg(−1) (0.125 μmol⋅min(−1)⋅mg(−1)). Y2, Y3, and Y4 isolated from E. coli have no measurable activity. Efforts to generate Y⋅ in Y2 or Y4 using Fe(2+), O(2), and reductant have been unsuccessful. However, preliminary studies show that incubation of Y4 and Fe(2+) with inactive E. coli Y2 followed by addition of O(2) generates Y2 with a specific activity of 0.069 μmol⋅min(−1)⋅mg(−1) and a Y⋅. A similar experiment with (His)(6)-Y2-K387N, Y4, O(2), and Fe(2+) results in an increase in its specific activity to 0.30 μmol⋅min(−1)⋅mg(−1). Studies with antibodies to Y4 and Y2 reveal that they can form a complex in vivo. Y4 appears to play an important role in diiron-Y⋅ assembly of Y2.